2015
DOI: 10.1016/j.jchemneu.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The centrally projecting Edinger–Westphal nucleus—I: Efferents in the rat brain

Abstract: The oculomotor accessory nucleus, often referred to as the Edinger-Westphal nucleus [EW], was first identified in the 17th century. Although its most well known function is the control of pupil diameter, some controversy has arisen regarding the exact location of these preganglionic neurons. Currently, the EW is thought to consist of two different parts. The first part [termed the preganglionic EW-EWpg], which controls lens accommodation, choroidal blood flow and pupillary constriction, primarily consists of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 62 publications
3
47
1
2
Order By: Relevance
“…In addition to the studies listed above, a set of comprehensive tracing studies investigating the ascending and descending projections of the EWcp have been performed recently in rats [91,92].…”
Section: Projections Of the Ewcpmentioning
confidence: 99%
“…In addition to the studies listed above, a set of comprehensive tracing studies investigating the ascending and descending projections of the EWcp have been performed recently in rats [91,92].…”
Section: Projections Of the Ewcpmentioning
confidence: 99%
“…Of special importance to us is the role of UCN1 in feeding behavior, as UCN1 acts as a powerful anorectic peptide in nanomolar concentrations (Spina et al, 1996) and diet/fasting can regulate Ucn1 mRNA expression (Legendre et al, 2007; Xu et al, 2009). Júnior et al (2015) have shown that UCN1-ir neurons or the EWcp send projections to the LHA and these fibers are in close proximity to MCH-ir neurons, so this UCN1|EWcp-MCH|LHA circuit could represent the pathway through which UCN1 influences feeding behavior. Although the low levels of CRF receptors in MCH could be taken as an evidence against this particular pathway, it is noteworthy that these receptors are found on the LHA (Chalmers et al, 1995), so the action of UCN1 could involve the modulation of GABAergic or GLUergic interneuronal input to MCH neurons.…”
Section: Feeding Behaviormentioning
confidence: 99%
“…CeA might be the major source of CRF projection to the BNST dl (Pomrenze et al, 2015). Alternatively, Ucn1 fibers originating from the Edinger Westphal nucleus (Dos Santos Junior et al, 2015) might modulate OT release in the BNST dl via CRFR1 and CRFR2. Therefore, some of the behavioral effects observed after CRF or Urocortins infusions into the BNST dl , may be, at least partially, a result of changes in extracellular OT content.…”
Section: Role Of the Bed Nucleus Of The Stria Terminalis (Bnst) In Thmentioning
confidence: 99%